A Typology of Management Studies Involving Culture - Adler, Nancy J. (Journal of International Business Studies, 1983)
As a methodological review, this paper delineates 6 approaches to researching cross-cultural management issues: parochial, ethnocentric, polycentric, comparative, geocentric, and synergistic. For each approach, assumptions are discussed concerning the similarity and difference across cultures and the extent to which management phenomena are or are not universal. The primary types of management questions which can be addressed using each approach are clarified. Main methodological issues which must be addressed are listed.